Triptycene-bis(aroyleneimidazole)s as non-fullerene acceptors: the missing links - Menke, Elisabeth H.; Leibold, David; Berger, Felix J.; Rominger, Frank; Vaynzof, Yana; Mastalerz, Michael (ChemPlusChem, 2017)
The syntheses of four triptycene-bis(aroyleneimidazole)s—the missing links with respect to the previously reported triptycene-mono(aroyleneimidazole)s and triptycene-tris(aroyleneimidazole)s—are presented. Their optoelectronic properties and use as non-fullerene acceptors in organic photovoltaics with poly(4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′]dithiophene-2,6-diyl[3-fluoro-2-(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl) (PTB7) as a donor are described; these systems reach a maximum power conversion efficiency of 2 %. Furthermore, the effect of molecular symmetry on the photovoltaic device performance is discussed.
Gesehen am 26.09.2018